Expression pattern of a nuclear encoded mitochondrial arginine-ornithine translocator gene from Arabidopsis - Catoni, Elisabetta; Desimone, Marcelo; Hilpert, Melanie; Wipf, Daniel; Kunze, Reinhard; Schneider, Anja; Flügge, Ulf-Ingo; Schumacher, Karin; Frommer, Wolf B. (BMC plant biology, 2003)
Arginine and citrulline serve as nitrogen storage forms, but are also involved in biosynthetic and catabolic pathways. Metabolism of arginine, citrulline and ornithine is distributed between mitochondria and cytosol. For the shuttle of intermediates between cytosol and mitochondria transporters present on the inner mitochondrial membrane are required. Yeast contains a mitochondrial translocator for ornithine and arginine, Ort1p/Arg11p. Ort1p/Arg11p is a member of the mitochondrial carrier family (MCF) essential for ornithine export from mitochondria. The yeast arg11 mutant, which is deficient in Ort1p/Arg11p grows poorly on media lacking arginine.